Adjektivbøyning i norsk – kongruenstilegnelse hos polskspråklige norskinnlærere - Janik, Marta Olga (Wydział Neofilologii UAM w Poznaniu, 2016)
The thesis gives an insight into the acquisition of adjective agreement by Polish learners of Norwegian as a second language basing on cognitive language acquisition theories. Its main aim is to show the Polish learners’ competence in inflecting the Norwegian adjectives by analyzing the correctly and incorrectly inflected adjectives, and to investigate factors that possibly influence the acquisition. The following factors are taken into consideration: 1) the linguistic factors (the grammatical context in which the adjectives were used, the inflectional paradigm of the adjectives), 2) the psycholinguistic factors (transfer), 3) the social factors (the general competences in Norwegian as a L2, age, education, the total number of course hours taken in Norwegian, length of stay in Norway, competences in English as a L3). The data used in this study come from the ASK corpus (The Norwegian Language Learner Corpus), where the participants wrote essays in a test situation. The analysis is based on 200 texts written by 200 L1 Polish learners of Norwegian. In the transfer investigation their performance is compared with the performance of 200 English and 200 German speaking learners of Norwegian.
Keywords: język norweski; odmiana przymiotników; kongruencja; korpus ASK; transfer; Norwegian; adjective inflection; agreement; ASK corpus; norsk; adjektivbøyning; kongruens; ASK-korpuset